THEORIZING DIASPORA: A READER (Editors: Braziel, Jana Evans & Mannur, Anita) - Raj, Aditya (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2004)
BRAZIEL, JANA EVANS & MANNUR, ANITA (Eds.) Theorizing Diaspora: A reader. Oxford Blackwell Publishing (2003). 345 pp. pb: C$29.95; hb: C$94.54. (ISBN- pb 063123392X. hb 0631233911).